Sumerian model contracts from the Old Babylonian period in the Hilprecht Collection Jena - Spada, Gabriella (Texte und Materialien der Frau Professor Hilprecht Collection of Babylonian Antiquities im Eigentum der Friedrich-Schiller-Universität Jena, 2018)
Cover; Title Page; Copyright; Table of Contents; Body; Vorwort des Herausgebers; Preface by the Author; 1. Introduction; 1. The texts; 2. Organization of the volume; 2. Catalogue and Concordance; Catalogue; Concordance of duplicates to the model contracts; 3. The text edition; 1. Prisms; Text n° 1.; Text n° 2.; Text n° 3.; 2. Type I tablet; Text n° 4.; 3. Type II tablets; Text n° 5.; Text n° 6.; Text n° 7.; Text n° 8.; Text n° 9.; 4. Unidentified type of tablets; Text n° 10.; Text n° 11.; 4. Indexes; 1. Personal names; 2. Deities; 3. Toponyms; 4. Glossary; a. Sumerian words; b. Akkadian word.